Why left and right-wing governments fail in Latin America. With a critique to Gabriel Palma. - Luiz Carlos Bresser-Pereira (Cuadernos de Economía, 2025)
Since 2019, a new wave of left-wing governments is happening in Latin America, but there is no reason to believe it will be successful. Since 1980, no governments either on the left or on the right have been economically successful. Quasi-stagnation – growing less than the other developing countries and less than the rich countries, falling behind – has been the rule. Gabriel Palma has drafted a recent paper present data and discussing this problem but offered no solution and ignored other Latin American contributions on the subject including New Developmentalism, which has an explication and a solution.